How to Check Integrity of Fiscal Data - Khemani, Pokar (IMF How To Notes; How-To Note ;, 2016)
The accuracy and reliability of government accounts and fiscal data is an issue in a number of countries, with significant and persistent discrepancies that can indicate underlying weaknesses in the country's public financial management system. This note provides guidance on how to detect issues with data quality, perform integrity checks, and reconcile fiscal data from various sources. It discusses the importance of reconciliation to provide reasonable assurance on the quality and reliability of government fiscal data, explores the main reasons for which discrepancies may arise, and explains how to conduct quality checks. The note concludes with recommendations for country teams of concrete steps to ensure data quality.